Comparison of methods for sustainable energy management with sewage sludge in Turkey based on SWOT-FAHP analysis - Adar, Elanur; Karatop, Buket; Ince, Mahir; Bilgili, Mehmet Sinan (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The sewage sludge creates as a result of wastewater treatment and has high water content, contains pathogens, heavy metals, micro-pollutants, etc., and also include organics that have a high calorific value, nitrogen and phosphor; therefore, it is necessary to select sustainable methods in its treatment/disposal. As for sustainable sludge management, not only current technologies, but also several other criteria such as legal regulations and problem-solving need to be taken into account. This study summarized the current situation for the management of domestic sewage sludge in Turkey and compared the methods of anaerobic digestion, incineration, gasification, pyrolysis and supercritical water gasification (SCWG), which are used/can be used in Turkey, with one another on the basis of four different criteria. As a result of the SWOT-FAHP (fuzzy analytic hierarchy process) analysis performed, it was observed that supercritical water gasification, which is one of the five methods considered, and problem-solving criterion, which is one of the four criteria considered, had the highest weight values. According to the results obtained via comparison of criteria, it was determined that the availability of current technology had less importance than problem-solving criterion in the selection of an appropriate method. The reasons why the method of supercritical water gasification had a high weight value even though it had certain disadvantages can be listed as follows: it ensures treatment with a high yield, does not require pre-treatment, has a shorter reaction time and creates a higher amount of beneficial by-products as compared with harmful emissions. Furthermore, this study also touched upon the obstacles to overcome for the development of SCWG and brought recommendations. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Sewage sludge; SWOT; Fuzzy analytic hierarchy process; Conventional methods; Supercritical water gasification; HYDROGEN-PRODUCTION; HYDROTHERMAL GASIFICATION; ANAEROBIC-DIGESTION; RENEWABLE ENERGY; MODEL COMPOUNDS; BIOMASS; TECHNOLOGIES; PYROLYSIS; JAPAN; Science & Technology - Other Topics; Energy & Fuels